“To Dear Deacon Kolya ...”: Newly Found Inscript of Sergey Yesenin - I. V. Kudryashov; S. N. Pyatkin (Научный диалог)
The results of a historical and cultural commentary on a previously unknown inscription by S. A. Yesenin, made by him in 1921 on a piece of paper, which was subsequently pasted into the book “Triptych” (Berlin: Publishing House “Scythians”, 1920), are presented. The scientific study of writers' dedicatory inscriptions as a separate area in domestic literary criticism is currently at the stage of its formation, which determines the relevance of the proposed study. It is proved that the addressee of Yesenin's dedication inscription is his elder friend and mentor in poetry Nikolai Alekseevich Klyuev (1884—1937) and it was made by the poet in December 1921 simultaneously with a short letter also addressed to Klyuev after a twoyear break in their creative communication. It is pointed out that Klyuev’s nickname “deacon Kolya” in Yesenin's script does not have negative connotations and serves as a playful, gentle definition of Klyuev’s mentoring role in Yesenin's poetic fate. An analysis of the structural and semantic connections of Yesenin's texts of the dedicatory inscription and letter makes it possible to establish that the inscription contains an implicit personal message for the renewal of former friendly relations between poets who have drifted away from each other due to creative differences. On the basis of Klyuev's reply message from Vytegra (January 28, 1922), it was established that Yesenin, at the end of December 1921, along with a letter, gave him his new books (including the “Triptych” containing poems of 1917) through Nikolai Ilyich Arkhipov (1887—1967) (a Vytegorsk acquaintance of Klyuev), who came to Moscow as a delegate to the IX All-Russian Congress of Soviets (December 23—28, 1921). It is put forward and substantiated that Yesenin, not being able to make a dedication to Klyuev on the book, sent an autographed sheet with Arkhipov for its subsequent pasting into the book. The authors of the article do not rule out that the pasting of Yesenin's inscription on the title page of the Berlin edition may have a later character. However, even so, it has an undoubted symbolic meaning, appealing to the Scythian philosophy, which united the poets in 1915—1917, being one of the signs of their spiritual kinship, the feeling of which Yesenin will carry through his entire creative life.